The pro-psychotic metabotropic glutamate receptor compounds fenobam and AZD9272 share binding sites with monoamine oxidase-B inhibitors in humans. (1st January 2020) - Varnäs, Katarina; Cselényi, Zsolt; Arakawa, Ryosuke; Nag, Sangram; Stepanov, Vladimir; Moein, Mohammad Mahdi; Johnström, Peter; Kingston, Lee; Elmore, Charles S.; Halldin, Christer; Farde, Lars
Abstract: The metabotropic glutamate receptor 5 (mGluR5) ligands fenobam and AZD9272 have been reported to induce psychosis-like adverse events and to bind at unknown, non-GluR5-related, sites. Based on similarities of the regional binding patterns for [ 11 C]AZD9272 and the monoamine oxidase-B (MAO-B) radioligand [ 11 C] L -deprenyl-D2 in PET studies of the human brain we tested the hypothesis that the unique binding of fenobam and AZD9272 may represent specific binding to the MAO-B. PET data previously acquired for subjects examined using [ 11 C]AZD9272 or [ 11 C] L -deprenyl-D2 were re-evaluated to assess the correlations between radioligand binding parameters in human brain. In addition, the pharmacology of AZD9272 binding sites was characterized using competition binding studies carried out in vivo in non-human primates (NHPs) and in vitro using autoradiography in selected human brain regions. The regional binding of [ 11 C]AZD9272 in human brain was closely correlated with that of [ 11 C] L -deprenyl-D2. In PET studies of NHP brain administration of the MAO-B ligand L -deprenyl inhibited binding of radiolabeled AZD9272 and administration of fenobam inhibited binding of [ 11 C] L -deprenyl-D2. Binding of radiolabeled AZD9272 in vitro was potently inhibited by fenobam or MAO-B compounds, and [ 11 C] L -deprenyl-D2 binding was inhibited by fenobam or AZD9272. The findings are consistent with the hypothesis that both fenobam and AZD9272 bind to the MAO-B, which may be of relevance for understanding the mechanism of the psychosis-like adverse events reported for these compounds. Such understanding may serve as a lead to generate new models for the pathophysiology of psychosis. Highlights: mGluR5 ligands fenobam and AZD9272 have been reported to bind at unknown sites. Binding of [ 11 C]AZD9272 is correlated with localization of MAO-B in human brain. Fenobam or MAO-B compounds inhibit binding of radiolabeled AZD9272. AZD9272 or fenobam inhibit binding of MAO-B radioligand [ 11 C] L -deprenyl-D2. Binding to MAO-B may possibly explain some adverse events of these compounds.